Electrochemical and Surface Morphological Studies of Carbon Steel Corrosion by a Novel Polynuclear Schiff Base in HCl Solution. (2nd December 2013) - Shaju, K. S.; Joby Thomas, K.; Raphael, Vinod P.; Paul, Aby
Abstract : The corrosion inhibition efficiency of a potential polynuclear Schiff base, (s)-2-(anthracene-9 (10H)-ylidene amino)-5-guanidinopentanoic acid (A9Y5GPA), on carbon steel (CS) in 1 M hydrochloric acid solution has been investigated using weight loss measurements, electrochemical impedance spectroscopy (EIS), and potentiodynamic polarization studies. The corrosion inhibition efficiencies of parent amine [(s)-2-amino-5-guanidinopentanoic acid] and parent ketone (anthracene-9 (10H)-one) on carbon steel in 1.0 M hydrochloric acid solution have also been investigated using weight loss studies. The electrochemical and weight loss data established that the inhibition efficiency on CS increases with the increase in the concentration of inhibitor, A9Y5GPA. The adsorption of A9Y5GPA obeys the Langmuir adsorption isotherm. Thermodynamic parameters (K ads, Δ G ads 0 ) were calculated using the adsorption isotherm. Activation parameters of the corrosion process (E a, Δ H * and Δ S * ) were also calculated from the corrosion rates obtained from temperature studies. Tafel plot analysis revealed that A9Y5GPA acts as a mixed-type inhibitor. A probable inhibition mechanism was also proposed. Surface morphology of the carbon steel specimens in the presence and absence of the inhibitor was evaluated by SEM analysis.